Kuwait : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Kuwait. (IMF Staff Country Reports; Country Report, 2022)
Sustained political gridlock has hobbled reforms and increased macroeconomic vulnerabilities, but a new high-level effort offers hope for resolving the impasse. The authorities have been preparing a comprehensive reform plan which, if adopted by parliament, would pave the way to address the structural and fiscal imbalances in the economy and promote sustainable and inclusive growth. The authorities responded swiftly and decisively to the COVID-19 crisis with social distancing restrictions and fiscal, monetary, and financial policy support measures. In 2021, a high rate of vaccination was achieved, although there has been a major surge in infections with the recent arrival of the Omicron variant. A nascent economic recovery is underway, supported by higher oil prices and some relaxation of mobility restrictions. However, substantial uncertainties to the economic outlook underscore the importance of phasing out COVID-19 relief measures at a measured pace as the economy recovers, and of accelerating the reform momentum to limit risks and rebuild buffers. Banks entered the crisis from a position of strength and have remained well capitalized and highly liquid.